Laribacter hongkongensis gen. nov., sp. nov., a Novel Gram-Negative Bacterium Isolated from a Cirrhotic Patient with Bacteremia and Empyema - Yuen, Kwok-Yung (American Society for Microbiology, 2001)
A bacterium was isolated from the blood and empyema of a cirrhotic patient. The cells were facultatively anaerobic, nonsporulating, gram-negative, seagull shaped or spiral rods. The bacterium grows on sheep blood agar as nonhemolytic, gray colonies 1 mm in diameter after 24 h of incubation at 37°C in ambient air. Growth also occurs on MacConkey agar and at 25 and 42°C but not at 4, 44, and 50°C. The bacterium can grow in 1 or 2% but not 3, 4, or 5% NaCl. No enhancement of growth is observed with 5% CO(2). The organism is aflagellated and nonmotile at both 25 and 37°C. It is oxidase, catalase, urease, and arginine dihydrolase positive, and it reduces nitrate. It does not ferment, oxidize, or assimilate any sugar tested. 16S rRNA gene sequencing showed that there are 91 base differences (6.2%), 112 base differences (7.7%), and 116 base differences (8.2%) between the bacterium and Microvirgula aerodenitrificans, Vogesella indigofera, and Chromobacterium species, respectively. The G+C content (mean and standard deviation) is 68.0% ± 2.43%, and the genomic size is about 3 Mb. Based on phylogenetic affiliation, the bacterium belongs to the Neisseriaceae family of the β-subclass of Proteobacteria. For these reasons, a new genus and species, Laribacter hongkongensis gen. nov., sp. nov., is proposed, for which HKU1 is the type strain. Further studies should be performed to ascertain the potential of this bacterium to become an emerging pathogen.